Filtenna-Oriented Mode Control and Resonance Fusion in Square SIW Cavities for 5G Millimeter-Wave Applications - Li, Jiawang ; 0000-0001-8186-5441; Cao, Yu Yan (IEEE Antennas and Wireless Propagation Letters, 2025)
This paper presents a single-layer filtering antenna (filtenna) based on a compact square substrate-integrated waveguide (SIW) cavity for millimeter-wave (mmWave) applications. The cavity operates in the fundamental TE110 mode to enable beam scanning, while a central shorting via introduces the TE210 mode, broadening the bandwidth. A radiating slot, placed at high-intensity regions of both modes, perturbs surface currents and facilitates efficient radiation. The resulting dual-mode resonance forms a bandpass response suited for mmWave communication. Two filtenna prototypes with different out-of-band suppression levels are implemented. Measurements show -10 dB impedance bandwidths of 7.1% (29.81-32.01 GHz) and 8.9% (29.05-31.74 GHz) for Filtenna I and II, respectively. Both designs exhibit stable radiation patterns with an average gain of approximately 4.9 dBi, and sideband rejections exceeding 25 dB at the lower side and 20 dB at the upper side. The proposed design eliminates the need for separate filtering circuits, thereby reducing system complexity and insertion loss. Its integration-friendly structure makes it particularly suitable for compact front-end modules in next-generation mmWave communication systems.
Keywords: Filtenna; mmWave; sideband rejection level; SIW